Impact of Long-Term Storage on Stability of Standard DNA for Nucleic Acid-Based Methods - Barbara Röder; Karin Frühwirth; Claus Vogl; Martin Wagner; Peter Rossmanith (2010)
ABSTRACT Real-time PCR is dependent upon a calibration function for quantification. While long-term storage of standards saves cost and time, solutions of DNA are prone to degradation. We present here the benchmark treatment for preservation of DNA standards, involving storage in 50% glycerol-double-distilled water, whereby a deviation of 0.2 threshold cycle ( C T ) values resulted after 100 days of storage.